Time-resolved detection of aromatic compounds on planetary surfaces by ultraviolet laser induced fluorescence and Raman spectroscopy. (15th December 2015) - Eshelman, E.; Daly, M.G.; Slater, G.; Cloutis, E.
Abstract: Raman spectroscopic instruments are highly capable in the search for organics on Mars due to the potential to perform rapid and nondestructive measurements on unprepared samples. Upcoming and future Raman instruments are likely to also incorporate laser-induced fluorescence (LIF) capabilities, which can be added for modest cost and complexity. We demonstrate that it is possible to obtain sub-ns fluorescence lifetime measurements of Mars-relevant organics and minerals if a fast time-gating capability is used with an intensified detector and a short ultraviolet laser pulse. This serves a primary purpose of discriminating mineral from short-lived (less than 10 ns) organic fluorescence, considered a potential biosignature. Additionally, lifetime measurements may assist in determining if more than one fluorescing species is present and provide information concerning the molecular structure as well as the local environment. Fast time-gating is also useful at longer visible or near-IR wavelengths, as this approach increases the sensitivity of the instrument to organic material by removing the majority of the fluorescence background from the Raman signal and reducing the effect of ambient light. Abstract : Highlights: Short-lived fluorescence, a possible biosignature, can be measured in situ. Fluorescence lifetime capabilities provide significant sensitivity to organics. PAHs, expected on Mars, fluoresce with characteristic spectra and lifetimes. Short-lived and long-lived fluorescence can be separated in mixed samples.